2004
DOI: 10.1029/2004jd004960
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of peroxycarboxylic nitric anhydrides (PANs) during the ITCT 2K2 aircraft intensive experiment

Abstract: [1] Measurements of peroxycarboxylic nitric anhydrides (PANs), peroxyacetic nitric anhydride (CH 3 C(O)OONO 2 ; PAN), and peroxypropionic nitric anhydride (CH 3 CH 2 C(O)OONO 2 ; PPN) were made in the spring of 2002, off the west coast of North America, as part of the Intercontinental Transport and Chemical Transformation 2002 (ITCT 2K2) project. Long-range transport of Asian emissions was observed in which PAN and PPN mixing ratios were as high as 650 pptv and 90 pptv, respectively. Moreover, these two specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 63 publications
(84 reference statements)
6
79
0
Order By: Relevance
“…The slope (or the ratio of PPN/PAN) of 0.152 was well within the range (0.135-0.172) reported in polluted areas (Grosjean et al, 1993;Kourtidis et al, 1993;Ridley et al, 1990). The VOCs precursors for PAN have been recognized to be emitted from both anthropogenic and biogenic sources whereas the precursors for PPN (propanal and 1-butene) are predominantly from anthropogenic sources (Grosjean et al, 2001;Roberts et al, 2004). Therefore, the ratio of PPN/PAN has been widely used as an indicator for distinguishing the contribution of anthropogenic hydrocarbons from biogenic hydrocarbons to atmospheric PANs.…”
Section: Correlation Between Pan and Ppnmentioning
confidence: 66%
See 2 more Smart Citations
“…The slope (or the ratio of PPN/PAN) of 0.152 was well within the range (0.135-0.172) reported in polluted areas (Grosjean et al, 1993;Kourtidis et al, 1993;Ridley et al, 1990). The VOCs precursors for PAN have been recognized to be emitted from both anthropogenic and biogenic sources whereas the precursors for PPN (propanal and 1-butene) are predominantly from anthropogenic sources (Grosjean et al, 2001;Roberts et al, 2004). Therefore, the ratio of PPN/PAN has been widely used as an indicator for distinguishing the contribution of anthropogenic hydrocarbons from biogenic hydrocarbons to atmospheric PANs.…”
Section: Correlation Between Pan and Ppnmentioning
confidence: 66%
“…Therefore, the ratio of PPN/PAN has been widely used as an indicator for distinguishing the contribution of anthropogenic hydrocarbons from biogenic hydrocarbons to atmospheric PANs. Through the regression of a linear multivariate correlation involving PAN and PPN, Roberts et al (2002Roberts et al ( , 2004 concluded that when the ratio of PPN/PAN is between 13.5% and 17.2%, PANs formation was dominated by anthropogenic hydrocarbons, while dominated by biogenic hydrocarbons when the ratio is lower than 10%. The average ratio of PPN/PAN (15.2%) obtained by this study implied that the PANs formation in Beijing was dominated by anthropogenic hydrocarbons emission.…”
Section: Correlation Between Pan and Ppnmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Experimental details regarding the various PAN data sets are reported by Parrish et al [1992], Jaffe et al [2001], Kotchenruther et al [2001a], and Roberts et al [2004], who estimated accuracies from 15 to 30% depending upon the study and the PAN levels. The 1985 study represent the only relatively early measurements, but fortunately two, wellrespected measurement groups simultaneously measured PAN, and the results agreed well [Parrish et al, 1992].…”
Section: Data Sets and Methods Utilizedmentioning
confidence: 99%
“…The most atmospherically abundant and well-understood of the APNs is acetyl peroxynitrate (PAN, CH 3 C(O)O 2 NO 2 ) formed from the oxidation of VOCs (Roberts, 2007;Fischer et al, 2014;Singh et al, 1992;LaFranchi et al, 2009;Moxim et al, 1996;Phillips et al, 2013;Roberts et al, 2004Roberts et al, , 2007Williams et al, 1997). Recent research has become increasingly focused on less-well-studied APNs due to their involvement in several key atmospheric processes.…”
Section: Introductionmentioning
confidence: 99%